Os clãs a partir do casal genearca Manoel Fernandes Penna (1776/77-1841) & Francisca Luiza de Lima (1788-1857) - Penna, Marco Antonio de Almeida (2013)
This paper studied about the ´guarda-mor´ MANOEL FERNANDES PENNA, central role of this work, and his wife FRANCISCA LUIZA DE LIMA, who settled in the central region o Rio Grande do Sul state, between 1806 and 1808. Aspects of geographical, social, economical and political trajectory of the family were reconstructed based on their first generations. It was studied the scenery of this couple and the formation of clans generated by their offspring from the biographical and genealogical inventory of their descendants and spouses. This study is in the area of concentration: History and Cultural Estate, and research line: Documental Heritage. It was aimed the clear out the clans from the reconstitution of parental bonds and the biography data. Once the genealogical matrix was being done, the bibliographical information was being taken. It was used as sources articles, dissertations and books on the local and regional historiography, baptism, wedding and death parish books from of Viamão, Santo Amaro, Cachoeira, Santa Maria, São Martinho and Cruz Alta, parish books which had the registration of lands and post mortem inventories from Cachoeira, Santa Maria, São Martinho, Júlio de Castilhos, Santo Ângelo and Cruz Alta, internet material and by interviewing some key‟ people. It was noticed: a) a fast, embracing, long lasting and intelligent insertion of the family in local and regional societies and a considerable social and economical development; b) a large number of descendants left by the patriarch couple and; c) the insertion of clans in the local and regional society, considering their comprehensiveness, activities and participation in society. Later, will be published the inventory biographical and genealogical of the descendants of the patriarch and the spouses (principal product) and on the scenery of their trajectory as well as the formation of the derived clans.